Organizational and Pedagogical Conditions of Formation of Key Competencies of Future Specialists in Aviation Transport Systems - Iryna Borets (Pedagogical Discourse, 2012)
In the article the organizational and pedagogical conditions of formation of key competencies of future specialists in transport systems in the aviation industry training are detected and grounded